2014
DOI: 10.1159/000368851
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Looping: A Key Principle of Chromatin Organization

Abstract: The effective volume occupied by the genomes of all forms of life far exceeds that of the cells in which they are contained. Therefore, all organisms have developed mechanisms for compactly folding and functionally organizing their genetic material. Through recent advances in fluorescent microscopy and 3C-based technologies, we finally have a first glimpse into the complex mechanisms governing the 3-D folding of genomes. A key feature of genome organization in all domains of life is the formation of DNA loops.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 155 publications
(251 reference statements)
1
24
0
Order By: Relevance
“…A key protein in nucleoid organization of Gram-negative bacteria is the Histone-like Nucleoid Structuring protein (H-NS). Genome-wide binding studies have revealed that H-NS binds along the genome in long patches ( Grainger et al, 2006 ; Kahramanoglou et al, 2011 ; Lucchini et al, 2006 ; Navarre, 2006 ; Oshima et al, 2006 ), which have been proposed to mediate the formation of genomic loops ( Noom et al, 2007 ; van der Valk et al, 2014 ). H-NS is also an important regulator of global gene expression, implied in mediating global transcriptional responses to environmental stimuli (osmolarity, pH, temperature) ( Atlung and Ingmer, 1997 ), and operating as xenogeneic silencer, silencing horizontally integrated DNA ( Navarre et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…A key protein in nucleoid organization of Gram-negative bacteria is the Histone-like Nucleoid Structuring protein (H-NS). Genome-wide binding studies have revealed that H-NS binds along the genome in long patches ( Grainger et al, 2006 ; Kahramanoglou et al, 2011 ; Lucchini et al, 2006 ; Navarre, 2006 ; Oshima et al, 2006 ), which have been proposed to mediate the formation of genomic loops ( Noom et al, 2007 ; van der Valk et al, 2014 ). H-NS is also an important regulator of global gene expression, implied in mediating global transcriptional responses to environmental stimuli (osmolarity, pH, temperature) ( Atlung and Ingmer, 1997 ), and operating as xenogeneic silencer, silencing horizontally integrated DNA ( Navarre et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mg 2+ alters H-NS structure. To investigate the role of Mg 2+ on individual H-NS dimers we carried out MD simulations of an H-NS dimer in both the absence and presence of Mg 2+ , using our previously established model of a full-length H-NS dimer 14 . Visual inspection of the H-NS dimer simulations at 50 mM KCl reveals that H-NS changes from an "open" extended conformation into more compact "closed" shapes (see figure 2a for snapshots from these simulations or figure 2 -figure supplement 2 for a movie of one such simulation).…”
Section: Resultsmentioning
confidence: 99%
“…The starting conformation of the full length H-NS dimer was constructed as described previously 14 . The system was placed in a periodic dodecahedron box with a distance of at least 0.8 nm between the box edge and the most extended atom of the protein dimer, followed by the addition of water and ions.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These loops may operate locally with regulatory functions at specific single genes [1,2], or over longer distances, enabling the organism to co-regulate genes that are in terms of genomic position far apart [3,4]. Although studies involving DNA looping have a rich history [3,[5][6][7][8][9][10][11][12], in recent years, numerous new insights have become available through the application of new biochemical and biophysical techniques.…”
Section: Introductionmentioning
confidence: 99%